2019
DOI: 10.1111/all.13728
|View full text |Cite
|
Sign up to set email alerts
|

Safety and reproducibility of nasal allergen challenge

Abstract: Background:The nasal allergen challenge (NAC) is a useful tool for the diagnosis of allergic rhinitis (AR) and local allergic rhinitis (LAR) and might serve to design and monitor allergen immunotherapy. Nevertheless, data about its safety and reproducibility are scarce.Objective: To investigate the safety and reproducibility of NAC in pediatric and adult rhinitis patients with/without asthmatic symptoms, and in healthy controls. Methods:A retrospective evaluation of the NACs conducted in our Unit for 2005-2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 38 publications
(77 reference statements)
1
45
0
8
Order By: Relevance
“…The NAC can be also considered positive if moderate changes occur simultaneously in both parameters [8]. In the above-mentioned study, we also report a very high reproducibility for the NAC (97.32%, PPV 100%, NPV 92.92%) when assessed by Lebel symptoms score and acoustic rhinometry [68]. This analysis was based on three consecutive NACs performed with the same allergen in 710 patients with 1–2-month interval, to avoid the evolution bias.…”
Section: Diagnosismentioning
confidence: 82%
See 2 more Smart Citations
“…The NAC can be also considered positive if moderate changes occur simultaneously in both parameters [8]. In the above-mentioned study, we also report a very high reproducibility for the NAC (97.32%, PPV 100%, NPV 92.92%) when assessed by Lebel symptoms score and acoustic rhinometry [68]. This analysis was based on three consecutive NACs performed with the same allergen in 710 patients with 1–2-month interval, to avoid the evolution bias.…”
Section: Diagnosismentioning
confidence: 82%
“…The NAC is the gold standard for LAR diagnosis, as it displays the optimal sensitivity and specificity [10,13,14]. A recent study from our group including data from 11499 procedures performed in 518 children and 5830 adults (1547 of them with asthma symptoms), demonstrated that the NAC is an extremely safe technique (99.97% of the procedures were well tolerated) [68]. Of note, the allergen administration by nasal spray or micropipette were equally safe [68].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…According to an EAACI position paper in 2017, potential biomarkers for monitorization of the clinical efficacy of AIT were summarized as follows: a) IgE (total IgE, sIgE/total IgE) b) subclasses of IgG (allergen‐specific IgG, IgG1 and sIgG4, sIgE/IgG4 ratio) c) IgE serum inhibitory activity for IgE (IgE‐FAB), d) basophil activation, e) chemokines and cytokines, f) cell markers such as Tregs, Bregs, and DCs, and g) in vivo biomarkers including provocation tests …”
Section: An Overview Of Allergen‐specific Immunotherapy Mechanismsmentioning
confidence: 98%
“…Both NAC-S and NAC-M protocols have proven to be safe. 49 Determining sIgE in nasal secretions is a noninvasive method and is highly specific; however, it has been found to have low sensitivity in most studies (22-40% of responses), a fact that can be attributed to the dilution effect, or other factors. 12,13 A recent study performed by Meng et al 50 found a quite high diagnostic accuracy for nasal sIgE in LAR diagnosis.…”
Section: Diagnostic Approach For Larmentioning
confidence: 99%